2020
DOI: 10.3390/su12031182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Authentic Leadership on Unethical Pro-Organizational Behavior: The Intermediate Role of Work Engagement

Abstract: Business ethics are an important part of corporate sustainability. Sustainability concerns not only the environment but also the well-being of employees, which includes work engagement. Authentic leadership has an impact on the work engagement and well-being of subordinates. The aim of the current research is to present the interdependencies between leadership, work engagement, and unethical pro-organizational behavior. A group of 623 employees from various organizations working in various positions in Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 80 publications
(97 reference statements)
2
32
0
Order By: Relevance
“…Moreover, scholarly interest in organization studies and managers have increased the effects of a leader's behavior on the follower's attitude/behavior, particularly in relation to innovation, which ultimately affects the sustainable growth of an organization [1,2]. Recent studies have indicated that the decisive role of the leader is required in order to initiate proactivity from employees-for innovation and to address complex problems in the process of innovation [3,4]. In this paper, we focus on the leader's feedback as a key factor in promoting employees' innovative behavior, by giving the employees more autonomy and psychological support in their work, thereby (eventually) increasing the sustainability of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, scholarly interest in organization studies and managers have increased the effects of a leader's behavior on the follower's attitude/behavior, particularly in relation to innovation, which ultimately affects the sustainable growth of an organization [1,2]. Recent studies have indicated that the decisive role of the leader is required in order to initiate proactivity from employees-for innovation and to address complex problems in the process of innovation [3,4]. In this paper, we focus on the leader's feedback as a key factor in promoting employees' innovative behavior, by giving the employees more autonomy and psychological support in their work, thereby (eventually) increasing the sustainability of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership has a significant effect on attitudes, behaviors, and various levels of performance [12,13], including the sustainability of organizations [14]. Recent studies on leadership have discussed sustainable leadership, which focuses on a leaders' attitude and behavior towards connecting organizations to innovation and systematic change as a response to the business environment, society, business ethics, and corporate responsibility [14][15][16]. The sustainable style of leadership is required to address the rapidly changing business environment and promote proactive actions of employees for organizational changes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that leadership can decrease employees’ engagement in UPB [ 15 , 16 ], while others indicate that it contributes to its increase [ 13 , 17 ]. Moreover, numerous studies have concluded that leadership causes employee engagement in UPB to increase through the moderating influence of various factors, such as the ethical climate [ 18 ], continuance commitment [ 19 ], work engagement [ 20 ], moral disengagement [ 21 ], reflective moral attentiveness [ 22 ], and organizational identification [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies on the relationship between leadership and UPB, the most frequently used theory is the theory of ethical leadership. To the best of our knowledge, authentic leadership has been studied only three times in the context of UPB [ 20 , 24 , 36 ]. Authentic leadership is a universally recognized concept that refers to management but is not limited to business [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%